STABILITY OF ISLAMIC BANK EFFICIENCY IN INDONESIA AND MALAYSIA: HAS COVID-19 MADE ANY DIFFERENCE? - Ihsanul Ikhwan; Ririn Riani (Bank Indonesia, 2023)
This study examines whether COVID-19 has affected the stability of Islamic banking efficiency in Indonesia and Malaysia using the Data Envelopment Window Analysis (DEWA) using data from 2017 to 2022. The findings indicate that Islamic banks in Malaysia exhibit a higher level of efficiency and stability as compared to their counterparts in Indonesia across all three efficiency measures, namely Technical Efficiency (TE), Pure Technical Efficiency (PTE), and Scale Efficiency (SE). In addition, the findings show that Islamic banks in both countries have stable efficiency performance over the period under investigation and hence the Covid-19 pandemic has not affected their efficiency levels. From the analysis, we further note that financing and labor costs are the main sources of inefficiency in Malaysian Islamic banks while fixed assets and operating revenue contribute the most to Indonesian Islamic banks’ inefficiency.